Hubungan Regulasi Emoai dengan Stres Akademik dalam Menyelesaikan Studi - Umi Latifatun Nadiyah; Frischa Meivilona Yendi (STKIP Subang, 2026)
Academic stress is a common problem frequently experienced by university students. A heavy academic workload can generate psychological pressure that develops into academic stress when it exceeds students' coping capacities. This study aimed to (1) describe the emotion regulation of final-year students in completing their studies, (2) describe the academic stress experienced by final-year students during the completion of their studies, and (3) examine the relationship between emotion regulation and academic stress among final-year students while completing their studies. This study employed a quantitative correlational design. The research population consisted of final-year students from the Department of Guidance and Counseling, Faculty of Education, Universitas Negeri Padang, cohorts 2019–2022, who were completing their studies. A total of 152 participants were selected using purposive sampling. Hypothesis testing was conducted using Pearson's product-moment correlation analysis at a 5% significance level. The results revealed a significant negative relationship between emotion regulation and academic stress (r = -0.319, p = 0.000, R² = 0.101). This indicates that higher levels of emotion regulation among final-year students are associated with lower levels of academic stress while completing their studies. Furthermore, the findings indicate that emotion regulation contributed 10.1% of the variance in academic stress, while other factors played a more dominant role.